Co-Administration of Vadimezan and Recombinant Coagulase-NGR Inhibits Growth of Melanoma Tumor in Mice - Amir Daei Farshchi Adli; Rana Jahanban-Esfahlan; Khaled Seidi; Davoud Farajzadeh; Ramezan Behzadi; Nosratollah Zarghami (Tabriz University of Medical Sciences, 2021)
Purpose: Tumor vascular targeting appeared as an appealing approach to fight cancer, though, the results from the clinical trials and drugs in the market were proved otherwise. The promise of anti-angiogenic therapy as the leading tumor vascular targeting strategy was negatively affected with the discovery that tumor vascularization can occur non-angiogenic mechanisms such as co-option. An additional strategy is induction of tumor vascular infarction and ischemia. Methods: Such that we used truncated coagulase (tCoa) coupled to tumor endothelial targeting moieties to produce tCoa-NGR fusion proteins. We showed that tCoa-NGR can bypass coagulation cascade to induce selective vascular thrombosis and infarction of mild and highly proliferative solid tumors in mice. Moreover, combination therapy can be used to improve the potential of cancer vascular targeting modalities. Herein, we report combination of tCoa-NGR with vascular disrupting agent (VDA), vadimezan. Results: Our results show that synergistic work of these two agents can significantly suppress growth of B16-F10 melanoma tumors in C57/BL6 mice. Conclusion: For the first time, we used the simultaneous benefits of two strategies for inducing thrombosis and destruction of tumor vasculature as spatial co-operation. The tCoa-NGR induce thrombosis which reduces blood flow in the peripheral tumor region. And combined with the action of DMXAA, which target inner tumor mass, growth and proliferation of melanoma tumors can be significantly suppressed.